Stomach Contents of Pangasius polyuranodon Bleeker (1852) from the Sail and Kampar Kiri Rivers Riau Province - Rica Pesta Graceli Pasaribu; Windarti Windarti; Eddiwan Eddiwan (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
AbstractPangasiuspolyuranodonisa type of freshwater fish that live in the Sail and Kampar Kiri River. This research aims to determine type of food present in the fish’sstomach. This research was carried out in Februarito March 2018. The fish were caught using nets and bamboo trap,once/ week. The number of fish caught during the study was 105, but 21 fisheshad empty stomach and they cannot be analyzed. The main food of P.polyuranodon in the Sail River is insects (IP 74.60%) plants (IP 7.56%),bivalva (IP5.85%), unidentified materials (IP 4.66%), fish (IP 4.24%) and crustaseans (IP 3.09%). Whereas in the Kampar Kiri River the main food of thefish is plants (IP 79.96%), insect (IP 11.42%), unidentified material (IP 5.55%) and fish (IP 3.07%). Data obtained indicate that P.polyuranodonisanomnivorous fish. Keywords: Main Food, Omnivorous Fish,Index of Preponderance, Feeding